Recovering religion: practising intersectoral cooperation in a time of cholera. Issue 5 (4th July 2017) - Braley, Matthew Bersagel
ABSTRACT: Due to social and historical forces resistant to predictions of religion's waning influence in the modern world, responses to contemporary epidemics continue to involve local religious entities and global religious networks. This viewpoint draws on the history of the 1854 cholera epidemic in London to highlight how histories of cooperation between religion and public health can help focus current thinking about the potential for intersectoral cooperation in response to modern epidemics.